PENURUNAN KADAR GLUKOSA PADA TIKUS HIPERGLIKEMI DENGAN ASUPAN TEMPE KORO BENGUK (Mucuna pruriens L) - Christiana Retnaningsih (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
A foodstuff that has a hypoglycemia potential is velvet beans (Mucuna pruriens L), espcially when it is in the form of a fermented product, i.e. tempe. The aim of study was toprove the effect of velvet beans tempe intake on blood glucose levelsThis research used randomized controlled group pre test- post test design using 50 maleSprague Dawley (SD) rats aged 2-3 months. The rats were subdivided into 5 groups, 10 rats pergroup, by means of random allocation. Group 1 is negative control (C-), group 2 is positivecontrol (C+), group 3 is X1-TK10%,  group 4 is X2-TK20%, group 5 is XTK30%. The groupsof C+, X1, X2, X33- are induced by 40 mg/kg body weight stereptozotocin dose by intra peritonealinjection. The research was conducted for 30 days. The data were analyzed with  One-wayAnova.The results showed that streptozotocin injection increased the level of blood glucose.Bioassay experiment demonstrated that velvet bean tempe diet reduced the level of bloodglucose in hyperglycemia rats.Key word :  Decreased glucose level, velvet bean tempe, hyperglycemia rat